Interreligious Marriage in Indonesia: Institutional Competition, Religious Monopolies, and the Dynamics of a Regulated Religious Economy - Muhammad Afdillah (Universitas Islam Internasional Indonesia (UIII), 2026)
This article examines interreligious marriage (IRM) in Indonesia as a politically contested arena within a regulated religious economy, where religious institutions, state agencies, courts, and intermediaries compete and collaborate to control access to marital legitimacy. Rather than treating IRM as a marginal anomaly or purely doctrinal issue, the study conceptualizes it as a structured site of negotiation shaped by legal pluralism, institutional competition, and political interests. Drawing on religious economy theory, Griffiths’ distinction between normative and empirical legal pluralism, and Bourdieu’s concept of the juridical field, the article analyzes how authority over marriage is distributed and contested across overlapping institutions. Empirically, the study is based on qualitative fieldwork conducted between 2022 and 2025 in Jakarta, Surabaya, and Biak, combining interviews with interreligious couples and institutional actors with legal and policy analysis. The findings highlight that Indonesia’s marriage regime operates as a state-supported religious monopoly restricting supply, generating alternative pathways, and producing adaptive strategies such as conversion, dual rituals, customary marriage, and court registration. The issuance of Supreme Court Circular (SEMA) No. 2/2023 marks a significant shift, closing judicial avenues and reinforcing religious authority. Interreligious marriage thus provides a critical lens for understanding the intersection of law, religion, and politics in contemporary Indonesia.